Bilingual advantages in foreign language learning: evidence from primary-school pupils with developmental language disorder - Tribushinina, Elena; Mackaaij, Megan (Frontiers in Education, 2023)
One of the bilingual advantages often reported in the literature on typically-developing children involves advantages in foreign language learning at school. However, it is unknown whether similar advantages hold for bilingual pupils with learning disabilities. In this study, we compare the performance of monolingual and bilingual primary-school children with developmental language disorder (DLD) learning English as a school subject in special education schools in the Netherlands. The participants were monolingual (N=49) and bilingual (N=22) children with DLD attending Grade 4−6 of special education (age 9-12). The bilingual participants spoke a variety of home languages. The English tests included a vocabulary task, a grammar test and a grammaticality judgement task. The Litmus Sentence Repetition Task and the Peabody Picture Vocabulary Test were used as measures of, respectively, grammatical ability and vocabulary size in Dutch (majority/school language). In addition, samples of semi-spontaneous speech were elicited in both English and Dutch using the Multilingual Assessment Instrument for Narratives. The narratives were analysed for fluency, grammatical accuracy, lexical diversity, and syntactic complexity. A questionnaire was used to measure amount of exposure to English outside of the classroom. The results for Dutch revealed no differences between monolinguals and bilinguals on the narrative measures, but monolinguals performed significantly better on both vocabulary and grammar. In contrast, bilinguals outperformed monolinguals on all English measures, except grammatical accuracy of narratives. However, some of the differences became non-significant once we controlled for amount of out-of-school exposure to English. This is the first study to demonstrate that foreign language learning advantages extend to bilingual children with DLD. The results also underline the need to control for differences in out-of-school exposure to English when comparing bilingual and monolingual pupils on foreign language outcomes.